Swadaya Masyarakat Membangun Sarana Prasarana Mengubah Kumuh Menjadi Wisata - wibowo, seno (Badan Koordinasi Kegiatan Kesejahteraan Sosial, 2023)
Change is an easy word and is often spoken but difficult to do. Everyone needs to make changes both from the individual to the environment that will have a good impact in poitic, social and economic terms. It takes recklessness and madness to make a change, as done by the people of Mrican Kelurahan Giwangan Kemantren Umbulharjo Yogyakarta City. They made the shabby riverside a tourist spot in the form of a children's playground and a fishery along a small river. The changes made by the mrican youth who named themselves “ mrican youth”. By doing simple thinking, unanimous determination and ignoring various rules, the change finally occurred. The economic leverage point is present in the form of Bendung Lepen Giwangan in a reckless, crazy and out of the book way and finally becomes the embryo of the masterplan in 45 Villages in Yogyakarta City